A chondrogenesis induction system based on a functionalized hyaluronic acid hydrogel sequentially promoting hMSC proliferation, condensation, differentiation, and matrix deposition. (1st March 2021) - Teng, Binhong; Zhang, Siqi; Pan, Jijia; Zeng, Ziqian; Chen, Yang; Hei, Yu; Fu, Xiaoming; Li, Qian; Ma, Ming; Sui, Yi; Wei, Shicheng
Abstract: Hydrogel scaffolds are widely used in cartilage tissue engineering as a natural stem cell niche. In particular, hydrogels based on multiple biological signals can guide behaviors of mesenchymal stem cells (MSCs) during neo-chondrogenesis. In the first phase of this study, we showed that functionalized hydrogels with grafted arginine-glycine-aspartate (RGD) peptides and lower degree of crosslinking can promote the proliferation of human mesenchymal stem cells (hMSCs) and upregulate the expression of cell receptor proteins. Moreover, grafted RGD and histidine-alanine-valine (HAV) peptides in hydrogel scaffolds can regulate the adhesion of the intercellular at an early stage. In the second phase, we confirmed that simultaneous use of HAV and RGD peptides led to greater chondrogenic differentiation compared to the blank control and single-peptide groups. Furthermore, the controlled release of kartogenin (KGN) can better facilitate cell chondrogenesis compared to other groups. Interestingly, with longer culture time, cell condensation was clearly observed in the groups with RGD and HAV peptide. In all groups with RGD peptide, significant matrix deposition was observed, accompanied by glycosaminoglycan (GAG) and collagen (Coll) production. Through in vitro and in vivo experiments, this study confirmed that our hydrogel system can sequentially promote the proliferation, adhesion, condensation, chondrogenic differentiation of hMSCs, by mimicking the cell microenvironment during neo-chondrogenesis. Graphical abstracta: Image, graphical abstract